Fixation augmented with micro-fragmented adipose derived stem cells (ORIF+) in simultaneous bilateral femoral shaft fracture: A pilot study - Rovere, Giuseppe; Smakaj, Amarildo; Rollo, Giuseppe; Ronga, Mario; Quassone, Pasquale; Perna, Andrea; Liuzza, Francesco; De Maio, Fernando; Fidanza, Andrea; Coviello, Michele; Cottone, Giuseppe; Maccagnano, Giuseppe; et al. (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Simultaneous bilateral femoral shaft fractures are extremely rare, high-energy injuries often associated with multiple systemic traumas. Intramedullary nailing remains the gold standard for diaphyseal femoral fixation, but alternative strategies may be required in complex or contraindicated cases. This pilot study aimed to assess the feasibility of open reduction and internal fixation biologically augmented with micro-fragmented adipose-derived stem cells (ORIF+) and to evaluate the reliability of the Radiographic Union Score (RUS) as a tool to monitor bone healing in simultaneous bilateral femoral fractures.Methods: Data from seven patients (14 femurs) with simultaneous bilateral femoral shaft fractures treated between 2016 and 2020 were analyzed. Each patient underwent intramedullary fixation in one limb and ORIF+ in the contralateral limb. Clinical outcomes were assessed using the Visual Analog Scale (VAS) for pain, and radiographic healing was quantified using the RUS on serial radiographs obtained postoperatively and at 1, 3, 6, and 12 months, then annually. The correlation between RUS and VAS was analyzed statistically.Results: All patients achieved complete bone union without complications. Both RUS and VAS scores showed progressive and significant improvement during follow-up. ORIF+ demonstrated higher RUS values and lower VAS scores at 3 and 6 months, suggesting enhanced early bone healing and pain control. Strong inter-observer agreement was observed for radiographic assessments (κ > 0.85).Conclusions: Open reduction and plate fixation augmented with micro-fragmented adipose-derived stem cells appears to be a safe and feasible biological alternative for managing complex femoral shaft fractures in selected cases. The Radiographic Union Score proved to be a reliable, reproducible, and objective method for assessing bone healing in this setting. Larger multicentric studies are needed to confirm these preliminary findings.